Potensi Biogas dan Pupuk dari Limbah Lumpur Kertas - Cindy Rianti Priadi; Iftita Rahmatika; Chihiya Fitria; Dwica Wulandari; Setyo Sarwanto Moersidik (Dept. of Chemical Engineering, Diponegoro University, 2016)
BIOGAS ENERGY AND FERTILIZING POTENTIAL FROM PAPER SLUDGE Paper sludge contains potential as energy and fertilizer due to the high amount of C, N and P. The aims of this study were to investigate resource recovery potential through biogas production from paper sludge only and with cow manure as co-substrate for 30-45 days in batch anaerobic digestion reactor. In addition, the fertilizer potential from digestate was also tested in Vetiveria zizanioides. Co-digestion with cow manure yielded higher methane gas up to 380 CH4/g VS due to a more optimum C/N ratio. Vetiver plants grown on digestate relatively showed the high growth performance after 4 weeks. The heavy metal accumulation from digestate was still in tolerable amount since the growth rate was not significantly different with the plant grown in fertilizer. Therefore, resource recovery technology can be an option to recover C, N and P in paper sludge to achieve sustainable waste management. Keywords: ananerobic digestion; biogas; fertilizer; paper sludge AbstrakLumpur dari Air Limbah industri kertas memiliki C, N dan P yang tinggi sehingga berpotensi menghasilkan energi dan menjadi pupuk, Penelitian ini bertujuan untuk meneliti pemulihan sumber daya (resource recovery) melalui produksi biogas dari lumpur kertas tanpa dan dengan ko-substrat kotoran sapi selama 30-45 hari dalam reaktor batch anaerobic digestion. Selanjutnya potensi pupuk dari digestat juga diuji dengan tumbuhan akar wangi (Vetiveria zizanioides). Setelah 45 hari, lumpur kertas dengan kotoran sapi menghasikan gas metana yang lebih besar, yaitu 380 CH4/g VS. Tanaman akar wangi yang ditanam dengan dengan digestat R2 tumbuh relatif tinggi setelah 4 minggu. Akumulasi logam berat juga masih dalam batas aman karena laju pertumbuhannya yang masih sebanding dengan tanaman yang diberi pupuk. Oleh karena itu, pemulihan sumber daya dapat diterapkan untuk memanfaatkan C, N dan P yang terkandung dalam lumpur kertas sebagai usaha pengelolaan limbah berkelanjutan. Kata Kunci: biogas; digestasi anaerobik; lumpur kertas; pupuk